Solve This cot-1(-x) = π - cot -1x but i want to show that cot-1(-x) = -cot​-1x ( why it is negative ) cot(-x) = ϑ   or -x = cot ϑ   or x = -cot ϑ   or  x = cot(- θ )  or -  ϑ = cot-1 x   or   ϑ = - cot -1x

Dear Student,
Please find below the solution to the asked query:

f-x=-fx holds only for odd functions like sinx, tanx , tan-1x, sin-1x etcAs cot-1x is not an odd function, hencecot-1-x-cot-1x

Hope this information will clear your doubts about this topic.

If you have any doubts just ask here on the ask and answer forum and our experts will try to help you out as soon as possible.

  • 1
What are you looking for?